Evaluasi Tata Kelola Teknologi Informasi Menggunakan Framework COBIT 5 Domain DSS (Deliver, Service, Support) (Studi Kasus : PT. PLN (Persero) Kantor Pusat) - A. Fahmi Baharuddin; Suprapto Suprapto; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Company sets an effective Information Technology Management in accordance with Ministerial Regulation of State-Owned Enterprises (SOEs) of 01/2011 Article 30 Section (1) and in reference to Ministerial Regulation of SOEs of 02/2013 Article 3 Section (1) and Section (5) in using and developing information technology to aim the objectives of the company. PT. PLN has an obligation to apply Good Corporate Governance, as mandated in Ministerial Regulation of SOEs of Per-01/MBU/2011 on application of Good Corporate Governance in SOEs. In conducting the business activities, PT. PLN requires the support of information technology operated in the form of software and hardware connected through data communication system of the company. With regards to information technology in PT. PLN, there are numbers of obstacles such as ineffective accident management on IT operational service which affecting the business activities. Based on the finding mentioned, an evaluation of information technology management of PT. PLN is required. This research uses COBIT 5 Domain Framework DSS (Deliver, Service, Support), to understand capability level and gap on information technology management of PT. PLN Head Office. The result of subdomain process of DSS01, DSS02, DSS03, DSS04, DSS05, DSS06 shows that capability level is on level 2, with gap value of 1 on DSS02, DSS05, DSS06 and no gap on DSS03, DSS04. In order to reach the expected target level, the recommendation are to increase supervision and documentation of work product and generic work product that are pertained to accident handling and accident management.